2016
DOI: 10.1111/bre.12175
|View full text |Cite
|
Sign up to set email alerts
|

Present‐day stress orientation in the Clarence‐Moreton Basin of New South Wales, Australia: a new high density dataset reveals local stress rotations

Abstract: Early phases of the Australian Stress Map project revealed that plate boundary forces acting on the Indo-Australian Plate control the long wavelength of the maximum horizontal present-day stress orientation in the Australian continent. However, all numerical models of the stress field to date are unable to predict the observed orientation of maximum horizontal stress in the northeast of New South Wales, Australia. Recent coal seam gas exploration in the Clarence-Moreton Basin, eastern Australia, provides an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 90 publications
(184 reference statements)
1
61
0
Order By: Relevance
“…Distinct rotations of breakouts near fractures by 90° in an otherwise relatively homogeneous rock mass and stable tectonic setting have been observed by Rajabi et al . []. Similar rotations over certain well sections were documented by Davatzes and Hickman [] in the 34‐9RD2 well at Coso.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Distinct rotations of breakouts near fractures by 90° in an otherwise relatively homogeneous rock mass and stable tectonic setting have been observed by Rajabi et al . []. Similar rotations over certain well sections were documented by Davatzes and Hickman [] in the 34‐9RD2 well at Coso.…”
Section: Discussionmentioning
confidence: 88%
“…Heterogeneity of stress in boreholes has been widely observed to correlate with natural fractures and faults [e.g., Bell et al, 1992;Shamir and Zoback, 1992;Barton and Zoback, 1994;Mariucci et al, 2002;Yale, 2003, Pierdominici et al, 2011Sahara et al, 2014;McNamara et al, 2015;Rajabi et al, 2015] and lithology changes [Wileveau et al, 2007]. A self-similar scaling of stress heterogeneity observed in boreholes has been first proposed by Shamir and Zoback [1992], and Day-Lewis et al [2010] aim to link this to the magnitude-frequency distribution of earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…In the studied wells, we observed localized rotation of breakouts in the vicinity of fractures and faults in the Taranaki Basin (Figure ). Such a local perturbation of the S Hmax was previously reported in the Taranaki Basin [ Camac et al ., ], and other regions worldwide, due to juxtaposition of different types of rocks, slip on active faults, and changes in the rock mechanical properties owing to high density of fractures [ Rajabi et al ., , ; Zoback , ]. It should be noted that local perturbations of breakouts in the studied wells occur in very short intervals (e.g., 10–15 m; Figure ) and do not have a significant impact on the mean S Hmax orientation.…”
Section: Results: Shmax Orientation Of the Taranaki Basinmentioning
confidence: 99%
“…The orientation of the S Hmax can be deviated from the regional trend, laterally and with depth, due to the presence of geological features [ Rajabi et al ., , ; Zoback , ]. The Taranaki Basin shows a significant ENE‐WSW S Hmax orientation except the west of Mount Taranaki where a number of close by indicators show rotations from the regional trend possibly owing to density contrast and magmatism as previously highlighted by Sherburn and White [].…”
Section: Discussionmentioning
confidence: 99%
“…Each of these studies, and numerous others that also observed various scales of S Hmax rotations occurring with depth in individual wellbores, have attributed these rotations to the presence of faults, fractures, or density contrasts, which cause localized perturbations in the stress field. Observations from both Rajabi et al (2017) and Lin et al (2010) indicate that abrupt changes of S Hmax are more consistent with the presence of faults, while gradual rotations of S Hmax are more consistent with the presence of fractures. Unfortunately, however, there is a 75 m gap between the two breakout zones that occur in Well 01, and in the absence of borehole televiewer logs, lithological logs, or information on local scale structures near Holly, we are unable to identify the cause of this rotation.…”
Section: Platform Holly-lateral and Depth Variations Of Shmaxmentioning
confidence: 89%